2003
DOI: 10.1046/j.1525-1594.2003.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Tsukuba Remote Monitoring System for Continuous‐Flow Artificial Heart

Abstract: In order to make long-term medical treatment with the use of an artificial heart effective, we developed the Tsukuba remote monitoring system, which enables medical staff to manage the physiological condition of patients and the driving condition of the artificial heart at anytime from a remote place. This remote monitoring system has three functions: first, a remote monitoring function, which enables medical staff to monitor measured data from a remote place anytime by using not only a personal computer but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 14 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…In the mock‐up circulation study, we confirmed the effective measurement performance of the developed mass flow meter. The developed mass flow meter would be essential not only to online monitoring of hospital patients, but also to the remote monitoring of discharged patients (10).…”
Section: Resultsmentioning
confidence: 99%
“…In the mock‐up circulation study, we confirmed the effective measurement performance of the developed mass flow meter. The developed mass flow meter would be essential not only to online monitoring of hospital patients, but also to the remote monitoring of discharged patients (10).…”
Section: Resultsmentioning
confidence: 99%
“…The animal experiments were conducted for 3, 15, 29, and 35 days. For the monitoring of the animal and the device during the test period, a remote monitoring system with Website and mobile phone was used (7).…”
Section: Methodsmentioning
confidence: 99%
“…The video signal of the front end of the system can directly enter the Ethernet and Intranet network. Authorized users can monitor the scene in anywhere through Web browsers [9,14]. It can access the Internet locally, and can also be remotely netted through a modem.…”
Section: Wenbo Fu and Debnath Narayanmentioning
confidence: 99%